The unexpected concentration-dependent response of periphytic biofilm during indole acetic acid removal. (May 2020) - Wang, Sichu; Ma, Lan; Xu, Ying; Wang, Yu; Zhu, Ningyuan; Liu, Junzhuo; Dolfing, Jan; Kerr, Philip; Wu, Yonghong
Highlights: IAA less than 10 mg/L inhibits the growth of periphytic biofilm. IAA more than 50 mg/L stimulates growth of periphytic biofilm. The removal rate of IAA by periphytic biofilm is 95%–100%. IAA more than 50 mg/L stimulates the capacity of periphytic biofilm to remove IAA. Abstract: Due to its extensive application in agriculture as a germinating agent and growth promoter, indole acetic acid (IAA) is present in a variety of aquatic ecosystems. To explore the response of microbial aggregates to exogenous IAA in aquatic ecosystems, periphytic biofilm, a typical microbial aggregate, was exposed to IAA at different concentrations. Results reveal an unexpected concentration-dependent effect of IAA on periphytic biofilm. Concentrations of IAA less than 10 mg/L inhibit periphytic growth, but stimulate growth when the IAA concentration exceeds 50 mg/L. Periphytic biofilm adapts to different IAA concentrations by antioxidant enzyme activation, community structure optimization and carbon-metabolism pattern change, and promotes bioremediation of IAA contaminated water in the process. The removal rates of IAA reached up to 95%–100%. This study reveals the capacity of periphytic biofilm for IAA removal in practice.